2016
DOI: 10.1002/prot.25029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the active site of human mitochondrial malonyl‐coenzyme a decarboxylase: A combined computational study

Abstract: Malonyl-CoA decarboxylase (MCD) can control the level of malonyl-CoA in cell through the decarboxylation of malonyl-CoA to acetyl-CoA, and plays an essential role in regulating fatty acid metabolism, thus it is a potential target for drug discovery. However, the interactions of MCD with CoA derivatives are not well understood owing to unavailable crystal structure with a complete occupancy in the active site. To identify the active site of MCD, molecular docking and molecular dynamics simulations were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In a search for compounds for the treatment of chronic kidney disease, Vitamin D receptor and cytochrome P450 were analyzed (Nagamani et al, 2016 ). Malonyl-CoA decarboxylase (Ling et al, 2016 ), sirtuins (Karaman and Sippl, 2015 ), adipocyte fatty-acid binding protein (Chen et al, 2014b ), 11β-hydroxysteroid dehydrogenase type 1 (Qian H. Y. et al, 2016 ), and protein tyrosine phosphatase 1B (Kocakaya, 2014 ) were reported for treatments of other metabolic diseases. For other diseases and disorders, targets such as pyrroline-5-carboxylate reductase for cutis laxa (Sang et al, 2017 ), renin complexes for hypertension (Tzoupis et al, 2015 ), and the type 1 receptor of TGF beta for wound healing (Gesteira et al, 2017 ) were examined.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…In a search for compounds for the treatment of chronic kidney disease, Vitamin D receptor and cytochrome P450 were analyzed (Nagamani et al, 2016 ). Malonyl-CoA decarboxylase (Ling et al, 2016 ), sirtuins (Karaman and Sippl, 2015 ), adipocyte fatty-acid binding protein (Chen et al, 2014b ), 11β-hydroxysteroid dehydrogenase type 1 (Qian H. Y. et al, 2016 ), and protein tyrosine phosphatase 1B (Kocakaya, 2014 ) were reported for treatments of other metabolic diseases. For other diseases and disorders, targets such as pyrroline-5-carboxylate reductase for cutis laxa (Sang et al, 2017 ), renin complexes for hypertension (Tzoupis et al, 2015 ), and the type 1 receptor of TGF beta for wound healing (Gesteira et al, 2017 ) were examined.…”
Section: Applications Of Mmpbsamentioning
confidence: 99%
“…Numerous studies have suggested that MLYCD may potentially be an effective treatment for cardiovascular diseases [25,26]. MLYCD regulates intracellular malonyl-CoA levels by converting malonyl-CoA into acetyl-CoA through decarboxylation, thereby exerting a major role in the regulation of fatty acid metabolism [27]. This mechanism may be highly relevant in the regulation of mitochondrial function.…”
Section: Co-localization Analysismentioning
confidence: 99%